Stellar distance and velocity (III) - Čojanović, Miloš (JOURNAL OF ADVANCES IN PHYSICS, 2021)
The use of parallax angles is one of the standard methods for determining stellar distance. The problem that arises in using this method is how to measure that angle. In order for the measurement to be correct, it is necessary for the object we are observing to be stationary in relation to the sun. This is generally not true. One way to overcome this problem is to observe the object from two different places at the same time. This would be technically possible but will probably never be realized. Another way to determine the distance is given in [1]. With certain assumptions, this is a mathematically completely correct method. After the publication of the third Gaia’s catalog [2], we are now able to test the proposed method using real data. Unfortunately, for the majority of stars it is not possible to obtain the distance directly, but with the help of some additional measurements we would be able to indirectly determine the distance of such stars.